Biodiesel production from Macro Algae as a green fuel for diesel engine - Ahmed, Abu Saleh; Khan, Sarfaraj; Hamdan, Sinin; Rahman, Md. Rezaur; Islam, Md Saiful; Maleque, Md. Abdul (2012)
Transesterification is an effective method to produce significant levels of biodiesel from renewable resources like plant oils and animal fats. Macroalgae is one of the inexpensive sources of oil feedstock for biodiesel production which is abundantly available in the sea areas. In this study algae oil was extracted from several types of macroalgae species namely L. Epiphytic, Cladophora, Agardhiella, Gracilaria, Spirogyra and Bryopsis Pennata. And their oils were then converted into biodiesel by the transesterification process. The extraction of algae oil from macroalgae was accomplished through Soxhlet method. The fuel properties of biodiesel was characterized through FTIR analysis and found to be similar chemical composition as to petroleum diesel. In addition, the highest yield was found (92%) at methanol to oil ratio 4:1, catalyst 1.0 wt% (KOH) in heating with stirring.